Development of an Augmented Reality-Based Comic Integrating Balinese Local Wisdom for Enhancing Elementary Students’ Learning Outcomes - Swarjawa, I Wayan Eka; Arnyana, Ida Bagus Putu; Gading, I Ketut (Jurnal Paedagogy, 2026)
This study aims to develop an Augmented Reality (AR)-assisted comic based on Balinese local wisdom to improve Indonesian language learning outcomes for third-grade elementary school students. The study employed a Research and Development method adapted from the ADDIE model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through questionnaires and learning outcome tests and analyzed using both qualitative and quantitative methods. Product validity was evaluated by experts in content, media, and language, while practicality was assessed by 15 students and 11 elementary school teachers. Effectiveness testing employed a Non-Equivalent Control Group Pretest–Posttest Design involving 19 students per group. The developed comic integrates Balinese local stories, particularly the traditions of Pengrupukan and Nyepi Day, into a child-friendly visual medium enriched with AR features, including simple animations, videos, audio narration, and supporting visual objects. The comic was designed based on the Indonesian Language Learning Outcomes for Phase B. The results indicate that the product is highly valid, with a validity coefficient of 1.00, and highly practical, with a practicality score of 92.68%. It was also effective in improving students’ learning outcomes, particularly in reading and listening comprehension, understanding story content, and information retention, as indicated by an N-Gain score of 0.79 and a Cohen’s d effect size of 1.78. In conclusion, the AR-assisted comic is valid, practical, and effective as an interactive and contextual learning medium for elementary school students.